Question

Asked Feb 27, 2020

1 views

Suppose F(x) = g(f(x)) and f(2) = 3, f'(2) = -3, g(3) = 5, g'(3) = 4. Find F'(2).

We are currently using the chain rule h(x) = g(f(x)) h'(x) = g'(f(x))f'(x)

The answer should be -12 but I have no clue how to set a problem like this up.

Step 1

We have to find F'(x) first using chain rule.

...Find answers to questions asked by student like you

Show more Q&A

Q: Evaluate the integral

A: Click to see the answer

Q: 16) Which function will shift y= vx right 4 units and up 1 unit? A) y = Vx + 4 +1 B) y = Vx + 1 C) y...

A: Click to see the answer

Q: Can you please answer this question and show the work

A: Click to see the answer

Q: Let f be the function defined as follows. y = f(x) = 3x2 − 3x + 6 (a) Find the differential of...

A: Click to see the answer

Q: Solve the nonlinear inequality. Express the solution using interval notation. (x + 9)2(x + 6) > ...

A: Click to see the answer

Q: 52. A car starts from rest and accelerates to a speed of 60 mph in 12 sec. It travels 60 mph for 1 m...

A: Click to see the answer

Q: 52. Show that a spherical cap of height h and radius R (Figure 19) has surface area 2n Rh. Rogawski ...

A: Click to see the answer

Q: Let if x 3 5 f(x) : and 8(4) = /fe f(t)dt Determine the value of each of the following: (a) g(-7) =...

A: Click to see the answer

Q: these are review questions for exam, i was absent when these were covered please help with #9 and #1...

A: Since you have submitted two questions, we'll answer the first question. For the second question ple...